Comparative oxidative stress, metallothionein induction and organ toxicity following chronic exposure to arsenic, lead and mercury in rats - Agrawal, S.; Flora, G.; Bhatnagar, P.; Flora, S. J. S. (Cellular and Molecular Biology, 2014)
Globally, arsenic, mercury and lead constitutes as the three most hazardous environmental toxicants perturbing imbalance in pro-oxidant and antioxidant homeostasis. Individual toxicity of these environmental toxicants is well known but there is lack of comparative data on variables indicative of oxidative stress. We thus investigated the effects of chronic exposure to sodium arsenite, mercuric chloride and lead acetate on blood and tissue oxidative stress, metal concentration and metallothionein (MT) contents. Male rats were exposed to sodium arsenite, mercuric chloride and lead acetate (0.05 mg/kg each, orally, once daily) for 6 months. Arsenic, mercury and lead exposure led to a significant inhibition of blood Î´-aminolevulinic acid dehydratase (ALAD) activity and glutathione level supported by increased thiobarbituric acid reactive substance (TBARS). The level of inhibition was more pronounced in case of lead followed by mercury and arsenic. These metals/ metalloid significantly increased reactive oxygen species (ROS), thiobarbituric acid reactive substances (TBARS) and glutathione peroxidase (GPx) activity accompanied by a decreased superoxide dismutase (SOD), catalase and reduced and oxidized glutathione (GSH and GSSG) levels in blood and tissues. Mercury alone produced a significant induction of hepatic and renal MT concentrations. Serum transaminases, lactate dehydrogenase and alkaline phosphatase activities increased significantly on exposure to arsenic and mercury exposure suggesting liver injury which was less pronounced in case of lead exposure. These biochemical alterations were supported by increased arsenic, mercury and lead concentrations in blood and soft tissues. The present study suggests that exposure to sodium arsenite and mercuric chloride lead to more pronounced oxidative stress and hepatotoxicity while lead acetate caused significant alterations in haem synthesis pathway compared to two other thiol binding metal/metalloid.